2010
DOI: 10.1556/imas.2.2010.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning is a method that may reduce the negative side-effect of pneumoperitoneum

Abstract: Increased intra-abdominal pressure during laparoscopy leads to hypoxia due to reduced blood flow. Aim of our study was to investigate whether preconditioning can reduce this negative effect of the pneumoperitoneum. Fifty female Wistar rats were used, divided into 5 groups. I: Sham operation (Sham), II: conventional pneumoperitoneum (PP), III: transvaginal pneumoperitoneum (TV), IV: preconditioning for 2.5 minutes in two cycles (Pre 2.5), V: preconditioning for 5 minutes (Pre 5). Malondialdehyde (MDA), reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…In our experiments, we created pneumoperitoneum conditions using a transvaginal approach due to the advantages of NOTES (Natural Orifice Transluminal Endoscopic Surgery) procedures, which are associated with less traumatic stress (14,23). Simultaneously, however, we wanted to achieve substantial oxidative stress, and therefore stressful levels of pneumoperitoneum pressure were applied (10 mmHg) (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, we created pneumoperitoneum conditions using a transvaginal approach due to the advantages of NOTES (Natural Orifice Transluminal Endoscopic Surgery) procedures, which are associated with less traumatic stress (14,23). Simultaneously, however, we wanted to achieve substantial oxidative stress, and therefore stressful levels of pneumoperitoneum pressure were applied (10 mmHg) (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently authors reported the effect of a 10-min ischemia postconditioning regimen (with 5 min of each-desufflation and insufflation), after pneumoperitoneum (7). The effect of postconditioning was evaluated by blood level analysis of oxidative stress markers and assessment of tissue morphology in animal models, which were initially established by our group (14). In the present study, we used a similar animal model and comparatively assessed two 10-min postconditioning regimens: a) Desufflation/insufflation for 5 min each; b) desufflation/insufflation for 2.5 min each-repeated twice (2 cycles).…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide-dismutase activity was higher in sham-operated rats than in rats with pneumo-peritoneum of 15 mmHg. The activity of protective enzymes can be stimulated by ischemic pre- or post-conditioning [ 133 , 134 ]. Both two cycles of a 2.5-min insufflation and a single cycle of 5 min increased the activities of superoxide-dismutase, myeloperoxidase, and attenuated the rise of malondialdehyde (marker of lipid peroxidation) after a 60-min pneumo-peritoneum of 10 mmHg in rats [ 133 , 135 ].…”
Section: Ischemic-reperfusion Injurymentioning
confidence: 99%
“…The activity of protective enzymes can be stimulated by ischemic pre- or post-conditioning [ 133 , 134 ]. Both two cycles of a 2.5-min insufflation and a single cycle of 5 min increased the activities of superoxide-dismutase, myeloperoxidase, and attenuated the rise of malondialdehyde (marker of lipid peroxidation) after a 60-min pneumo-peritoneum of 10 mmHg in rats [ 133 , 135 ]. Parallel to these changes, no effect was detected on the inflammatory-response-associated tumor necrosis factor α (TNF-α) levels.…”
Section: Ischemic-reperfusion Injurymentioning
confidence: 99%
“…Μικρότερου βαθμού ήταν και οι ιστικές βλάβες που παρατηρήθηκαν μετά από ισχαιμική προετοιμασία, με πιο εμφανή αποτελέσματα στο ήπαρ. Η προστασία δε που προσφέρει είναι τόσο σημαντική που πολλά από τα αποτελέσματα δεν είχαν στατιστικώς σημαντικές διαφορές με την ομάδα ελέγχου (ομάδα S), όπως είναι οι ιστικές βλάβες στο ήπαρ και στο έντερο, τα αποτελέσματα της αναγωγάσης της γλουταθειόνης και της μυελουπεροξειδάσης του ορού.Τα αποτελέσματα της μελέτης μας είναι αντίστοιχα άλλων προηγούμενων πειραματικών μελετών με ισχαιμική προετοιμασία σε πνευμοπεριτόναιο358,442,443 . 25% επίμυος) μονοκλωνικό IG1 αντίσωμα εναντίων του TNF-α, κατασκευασμένο με τεχνικές ανασυνδυασμού, έχει υψηλή συνάφεια με διαλυτά μόρια TNF-α και με τους μεμβρανικούς υποδοχείς του6 .…”
unclassified